A questão da diferença na sociedade contemporânea: reflexões a partir de zygmunt bauman - Silva, Rafael Bianchi; Carvalho, Alonso Bezerra de [UNESP] (My University, 2014)
The objetive of this article is discuss the question of difference and alterity presents in analyzes of contemporary society conducted by the polish sociologist Zygmunt Bauman. The author observed that human relations are guided by a logic of cost-benefit connected with values of present in the discardability of consumer society. At the same time, it has built ways of eliminating difference through the construction of a politics of expulsion of those considered strangers. For the author, the cities are the materialization of the ambivalence of live with the other people in contemporary times, being the locus of experience approach and retraction to the other expressed by fear of the difference. The result of this process is the impoverishment relational, the feeling of loneliness and an ethical-political crisis seen that could be seen from the primacy of the private/intimate rather than the public dimention/action.

O objetivo deste artigo é discutir a questão da diferença e da alteridade a partir das análises da sociedade contemporânea realizadas pelo sociólogo polonês Zygmunt Bauman. O autor observa que as relações humanas estão pautadas pela lógica de custobenefício, atrelada a valores de descartabilidade presentes na sociedade de consumo. Ao mesmo tempo, tem-se construído formas de eliminação da diferença através da construção de uma política de afastamento daqueles que são considerados estranhos. Para o autor, as cidades são a materialização da ambivalência de estar com o outro na contemporaneidade, sendo o locus de vivência de aproximação e afastamento do outro expressados pelo medo à diferença. Como resultado desse processo, encontra-se o empobrecimento relacional, o sentimento de solidão e uma crise ético-política observada a partir primazia do privado/intimidade em detrimento à dimensão/ação pública.
Keywords: Zygmunt Bauman; Contemporary Society; Difference; Zygmunt Bauman; Contemporaneidade; Diferença